2013
DOI: 10.1007/s10120-013-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of endoscopic submucosal dissection for early gastric cancer: a retrospective comparison with conventional endoscopic resection in a single center

Abstract: Background Few studies have compared the outcomes of endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) in patients with early gastric cancer. Methods We studied 780 lesions for which endoscopic treatment was indicated according to the Japanese Gastric Cancer Association (JGCA) criteria or the Results The median follow-up was 73 months in the EAM group and 65 months in the ESD group. Overall, the local recurrence rate was significantly lower in the ESD group (0.2 %, 1/421) than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 18 publications
1
72
3
1
Order By: Relevance
“…However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study. Oda et al [12] also reported the favorable long-term outcomes of curative gastric ESD over follow-up periods of at least 5 years; however, they reported preliminary results of a multicenter questionnaire survey without collecting individual patient data, meaning that they could not estimate the long-term outcomes using the Kaplan-Meier method.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study. Oda et al [12] also reported the favorable long-term outcomes of curative gastric ESD over follow-up periods of at least 5 years; however, they reported preliminary results of a multicenter questionnaire survey without collecting individual patient data, meaning that they could not estimate the long-term outcomes using the Kaplan-Meier method.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, ESD has been performed to treat EGCs, including large and ulcerative lesions, and there have been a number of published reports on the short-and long-term outcomes of ESD for EGC [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, there are few published reports on the long-term outcomes with median follow-up periods of over 5 years ( [10,11,13] reported favorable long-term outcomes of gastric ESD with median follow-up periods of over 5 years; however, the number of cases included in those studies was fewer than the number included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) stated that endoscopic resection for these tumors was regarded as an investigational treatment and ESD should be employed [3]. Excellent long-term outcomes of ESD for EGC that fulfilled the foregoing criteria were reported [5][6][7][8][9][10][11][12]. Although these were retrospective studies, the expanded pathological criteria have been considered acceptable.…”
Section: Case Reportmentioning
confidence: 99%
“…Since the early twenty-first century, clinical staging assessments have been considered important becasue of the increased diversity of treatment modalities such as endoscopic submucosal dissection [5], limited surgery for early cancer, and multimodality treatments, including neoadjuvant chemotherapy, for advanced cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%